翅片滚刀参数化设计系统的研究与开发 - 沈铭乾; 武宝林; 田冬龙 (Jixie chuandong)
Under the VS C++platform,with the modularized design concept and the Pro/TOOLKIT that provided by Pro/E 5.0software,the parametric design and Pro/E re-development of the fin hobs carried out.As well as through ADO database access interface technology,the communication and data exchange between the each modular and ACCESS database is realized.The design system includes rights management,parameter calculation and 3Dmodels auto-modeling and other functional modules.All above mention works lay a foundation for the fin hobs accurate and efficient design.